Nanofabricated solid immersion lenses registered to single emitters in diamond - Marseglia, L; Hadden, J; Stanley-Clarke, A; Harrison, J; Patton, B; Ho, Y; Naydenov, B; Jelezko, F; Meijer, J; Dolan, P; Smith, J; Rarity, J; et al. (2011)
We describe a technique for fabricating micro- and nanostructures incorporating fluorescent defects in diamond with a positional accuracy better than hundreds of nanometers. Using confocal fluorescence microscopy and focused ion beam etching, we initially locate a suitable defect with respect to registration marks on the diamond surface then etch a structure using these coordinates. We demonstrate the technique by etching an 8 μm diameter hemisphere positioned with single negatively charged nitrogen-vacancy defect lies at its origin. Direct comparison of the fluorescence photon count rate before and after fabrication shows an eightfold increase due to the presence of the hemisphere. © 2011 American Institute of Physics.